Effect of Phosphorus and K_Humate on Phosphorus uptake, growth rates and cobs characteristics of corn (Zea mays. L) in Calcareous Soil - علوش, غياث; زينة, ربيع; حتى, أسامة (Latakia University Journal -Biological Sciences Series, 2022)
A field experiment was conducted in a calcareous soil (CaCO3 = 49.7%) during 2018 season at Stkheres Research Station in Lattakia to study the effect of humate (0 and 25 kg K-humate/ha) on the response of maize crop (tango hybrid) to TSP application (0 - 30 - 60 - 90 - 120 - 240 kg / ha). The experiment therefore consisted of 12 treatments with three replicates, and plots were completely randomized. Growth and P uptake were followed on complete selected plants at 56 and 101 day from sowing, corresponding to VT and V6 phonological stages. At harvest (after 101 day), productivity of grain and indicators of ears are taken. A significant effect of phosphate fertilizer was observed on plant height and increase in dry weight of plants during all growth stages. The effect of humates on plant height was significant at VT stage. Phosphorous uptake was higher in plants receiving low TSP fertilization (≤ 60 kg TSP/ha) and humates compared to the same TSP treatments without humate. The differences in P-uptake were clearer in advanced growth stages which reached in control P0HA1 (107.2, 213.4 and 465.2 mgP/plant) in stages V8-10, VT and R2, respectively. These values ​​were higher compared to treatment control P0HA0 by 25%, 4% and 13% respectively. Maize amendment with humate and 240 kg TSP/ha had a significant increase in growth rate CGR than other treatments compared to the control P0HA1 and P0HA0 by about 35% and 49%, respectively. The P-uptake was almost linearly associated with the increase in the CGR throughout the whole life stages of the plant. This ultimately contributed to an increase in the weight and size of the ears, the number of grains in rows, and weight of a thousand grain.